(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2005)
Extraction of the constituents of total plant (aerial parts and roots) of Moquinia kingii afforded three flavonoids described for the first time in the tribe Moquinieae. In addition sesquiterpene lactone and triterpenes were isolated. Structures were established by spectroscopic studies.